Source Determination of Debris Avalanche Deposit based on the Morphology and Distribution of Hummocky Hills on the Northeastern Flank of G. Sundoro and G. Sumbing, Central Java, Indonesia - Rahayu, Eti; Wibowo, Haryo Edi; Moktikanana, Mradipta Lintang Alifcanta; Setianto, Agung; Harijoko, Agung (Indonesian Journal of Geography, 2023)
The presence of hummocky hills as a typical product of debris avalanche deposits is prominently visible in the northeastern flank of G. Sundoro and G. Sumbing, Temanggung, Central Java. In an attempt to better understand the past behavior of both G. Sundoro and G. Sumbing, we identify the source of the debris avalanche deposit. Interpretation is performed on the basis of the assumption of two possible sector collapse sources, i.e., G. Sundoro and G. Sumbing. The Sumbing source scenario is assumed as freely spreading type considering 1) distribution of the hummocky hills are relatively on the northeastern flank of the volcano, and 2) the present crater structure on the summit of the volcano which is opening to the northeast. The Sundoro source scenario is assumed as valley-filling type considering the distribution of the hummocky hills are relatively on the eastern flank of Sundoro extended to the far distal area and bounded by older high topography of G. Sumbing and North Serayu Mountains. The source identification was done on the basis of field observation of the deposit lithological characteristics combined with image analysis, including hummocky hills morphometry, displacement angle, and spatial distribution. Image analysis identifies approximately 645 hummocky hills ranging from 1,851 mz to 623,828 mz and average of 23,482 m2. Petrographic analysis of 5 representative block lava samples shows variation of olivine basalt, pyroxene andesite, to hornblende andesite. The results show that big size hummocky hills dominate the western side, while small size on the east. Displacement angle varied following the valley orientation with typical downslope topography. These suggested that the hummocky hills were originated from G. Sundoro as a valley-filling debris avalanche deposit.